Dr. Milind Kachare — Deep Plane Facelift — St. Louis - Kachare, Milind (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Milind Kachare, practicing in St. Louis, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003432; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; st. louis